Emerging Technologies in Multi‐Material Bioprinting. Issue 49 (1st October 2021) - Ravanbakhsh, Hossein; Karamzadeh, Vahid; Bao, Guangyu; Mongeau, Luc; Juncker, David; Zhang, Yu Shrike
Abstract: Bioprinting, within the emerging field of biofabrication, aims at the fabrication of functional biomimetic constructs. Different 3D bioprinting techniques have been adapted to bioprint cell‐laden bioinks. However, single‐material bioprinting techniques oftentimes fail to reproduce the complex compositions and diversity of native tissues. Multi‐material bioprinting as an emerging approach enables the fabrication of heterogeneous multi‐cellular constructs that replicate their host microenvironments better than single‐material approaches. Here, bioprinting modalities are reviewed, their being adapted to multi‐material bioprinting is discussed, and their advantages and challenges, encompassing both custom‐designed and commercially available technologies are analyzed. A perspective of how multi‐material bioprinting opens up new opportunities for tissue engineering, tissue model engineering, therapeutics development, and personalized medicine is offered. Abstract : A comprehensive overview of the available 3D bioprinting technologies for fabricating multi‐material constructs is presented. The technologies are classified into four major categories, and their advantages and shortcomings are compared. Available multi‐material commercial bioprinters are reviewed, concluding with a perspective of the future path for developing multi‐material technologies.